O consumo de gordura trans durante a gestação e lactação de ratas modifica parâmetros de adição à morfina dos filhotes durante a adolescência - Roversi, Karine (2017)
The consumption of processed foods that are rich in saturated and trans fat acids can modify the phospholipidic composition of the neural membranes. Thus, altering their plasticity and neurotransmission, the fatty acids (FA) that compose these membranes come from the diet, especially during the brain development period. Studies has shown that chronic consumption of trans fat during the early stages of life may facilitate the development of addiction to psychostimulant drugs. On the other hand, the gender, which has already shown the differences in behavioral and neurochemical response to addictive drugs, also has an influence on the development of addiction, although, the data are controversy. In the last years, addition to opioids has become a serious public health problem, since the number of addicted people and overdose deaths have grown alarmingly. The objective of this study was to evaluate the influence of maternal intake of hydrogenated vegetable fat (HVF) rich in trans FA during gestation and lactation on parameters of anxiety and morphine addiction (4 mg/kg), a recognized opioid of clinical use, in adolescent male and female pups. In addition, the generation of reactive species (RS) in brain areas involved with addiction was evaluated. The results showed that females of the HVF group showed higher preference to morphine and less anxiety behavior when compared to males of the same experimental group. Also, was observed that supplementation with HVF in both sexes increased per se the generation of RS in the ventral tegmental area (VTA), whereas administration of morphine did not modify this oxidative parameter. After administration to morphine, only females of the HVF group showed increased levels of RS in the hippocampus when compared to males. From these results, we can suggest that the gender can be considered a predisposing factor for the opioid addiction development, given that females showed a higher preference for the drug. Moreover, maternal trans fat consumption in the pups' developmental periods also modified parameters to morphine addiction, possibly due to the incorporation of trans FA in the phospholipids of the brain neural membranes, affecting the opioid system and oxidative status of brain areas related to addiction.